Comparative Case Study on Oscillatory Behavior in Power Systems of Marine Vessels With High Power Converters - Tarasiuk, Tomasz; Jankowski, Piotr; Shagar, Viknash; Piłat, Andrzej; Górniak, Mariusz; Nowak, Jarosław (Frontiers in Energy Research, 2021)
The chief aim of the proposed paper is to compare the behavior of supply voltage registered onboard three vessels equipped with high power converters during normal operation. The vessels considered are a chemical tanker with shaft generator working via power converter, a research-training ship with bow thruster, and a research vessel with dynamic positioning (DP) and electrical propulsion. In the case of the two latter ships, power electronic loads are present, which include a bow thruster adjustable speed drive equipped with the six pulse uncontrolled rectifier and the adjustable speed drive with an active front end (AFE) for propulsion system. For each ship, instantaneous frequency is determined and subsequently fluctuations of fundamental components and chosen harmonics are calculated using zoom-DFT. The characteristics of these irregular fluctuations are compared and commented on. Next, phase portraits and Poincare map of the registered voltages are calculated and compared. Moreover, the impact of ship rolling and pitching on the oscillatory behavior is assessed for the DP ship. The final conclusions identify reasons for oscillatory behavior in electric power systems of marine vessels containing high power converters on the source side and load side. The feasibility of using voltage trajectories as well as Poincare maps for oscillatory behavior detection is assessed.